2009
DOI: 10.1021/ja906135d
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the ADP-Ribosylation Sites in the PARP-1 Automodification Domain: Analysis and Implications

Abstract: Poly(ADP-ribose) polymerase-1 (PARP-1) is a multimodular (domains A, B, C, D, E, and F) nuclear protein that participates in many fundamental cellular activities. Stimulated by binding to nicked DNA, PARP-1 catalyzes poly(ADP-ribosyl)ation of the acceptor proteins and itself using NAD(+) as a substrate. Early studies suggested that domain D is likely an interface for protein-protein interaction between PARP-1 and its targets and is also the primary region for automodification. However, determination of the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
129
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(137 citation statements)
references
References 21 publications
5
129
0
1
Order By: Relevance
“…Mutational analysis in the work of Altmeyer et al (23) led to the identification of three lysine residues in the PARP-1 auto-modification domain (Lys 498 , Lys 521 , and Lys 524 ) as the sites of ADP-ribosylation. Recently, the first successful identification of the ADPribosylation sites in PARP-1 was done by mass spectrometry (27). In this study, the glutamic and aspartic acid residues in the PARP-1 auto-modification domain (Glu 488 , Glu 491 , and Asp 387 ) were identified as the acceptor amino acid residues.…”
Section: Discussionmentioning
confidence: 96%
“…Mutational analysis in the work of Altmeyer et al (23) led to the identification of three lysine residues in the PARP-1 auto-modification domain (Lys 498 , Lys 521 , and Lys 524 ) as the sites of ADP-ribosylation. Recently, the first successful identification of the ADPribosylation sites in PARP-1 was done by mass spectrometry (27). In this study, the glutamic and aspartic acid residues in the PARP-1 auto-modification domain (Glu 488 , Glu 491 , and Asp 387 ) were identified as the acceptor amino acid residues.…”
Section: Discussionmentioning
confidence: 96%
“…[22][23][24] Dimerization is assumed to be a prerequisite for PARP-1 activation 25 ; however, the AMD deletion mutant is catalytically active, indicating that this segment is not indispensable for PARP-1 activity. 20 Other studies 24,25 have suggested that interaction in the N-terminal region is required for PARP-1 dimerization and activation. The structural basis and significance of PARP-1's dimerization for its catalytic activity are not yet clear.…”
Section: Parp-1 Structure Properties and Activationmentioning
confidence: 99%
“…There are several glutamic acid residues in this domain that are suggested to be the site for covalent binding with poly(ADP-ribose) on PARP-1 activation. 19,20 However, other groups argue that individual lysine residues, not glutamic acid, serve as acceptor sites for ADP ribosylation in the AMD. 21 The PAR modification of glutamic residues in the NAD ϩ -binding domain and the DBD has also been noted.…”
Section: Parp-1 Structure Properties and Activationmentioning
confidence: 99%
See 2 more Smart Citations